Understanding the role of emotion regulation strategies in cybervictimization and cyberaggression over time: It is basically your fault! - Quintana-Orts, Cirenia; Mérida-López, Sergio; Rey, Lourdes; Chamizo-Nieto , María Teresa; Extremera, Natalio (Cyberpsychology: Journal of Psychosocial Research on Cyberspace, 2023)
Adolescents involved in experiences of cybervictimization and cyberbullying are at increased risk of psychological maladjustment and ill-being. However, not all adolescents involved in cyberbullying roles experience similar consequences and cognitive emotion regulation (CER) might be a key factor. Despite growing interest in the role CER strategies play in cyberbullying behaviours, little is known about the predictive utility of these strategies in predicting cybervictimization and cyberbullying over time. Therefore, the aim of this prospective study was to test the incremental predictive validity of specific CER strategies in cybervictimization and cyberbullying in a sample of adolescents. To this end, data were collected in two waves four months apart from a sample of 841 adolescents (466 females) aged 12 to 18 (MageT1 = 13.77, SDT1 = 1.34; MageT2 = 13.71, SDT2 = 1.31). Participants filled out a set of questionnaires measuring cybervictimization, cyberbullying, and CER strategies. Main results showed blaming others as the unique strategy showing incremental predictive value to both cybervictimization and cyberbullying four months later, above and beyond previous cybervictimization and cyberbullying experiences. Overall, the results highlighted the need to account for CER strategies, such as blaming others, in relation to the potential initiation and development of cyberbullying and cybervictimization behaviours. These findings suggest possible future avenues for intervention efforts targeting the maintenance of online aggressive behaviours and victimization across time.